Memperkuat Eksistensi Hukum Adat Melayu di Melayu di Kabupaten Batu Bara - Hasibuan, Abdul Latif; Faiz, Muhammad Afif; Arnanda, Bayu; Harahap, Herlina Hanum (VISA: Journal of Vision and Ideas, 2025)
The problem discussed in this research is how the ethnic identity of the Batu Bara Malay community is influenced by cultural construction in Batu Bara Regency. The results of the research show that the coal Malay community has highlighted their coal Malay identity with forms of social interaction through the language used in daily life, ethnic symbols, customs, as well as Batu Bara government policies in maintaining the Batu Bara Malay identity in Batu Bara Regency. The Batu Bara Malay tradition, which is still strong and inherent, makes the Batu Bara Malay people express their "I" nature wherever they are. However, with the many ethnic groups in Batu Bara, the reciprocal relations for the coal community are harmonious and there are still cooperative relations between tribes, even these differences do not become a barrier in society.